Investigating the signalling and functional activity of CD24 in cancer - Otifi, Hassan (2017)
Background and Aim: The cluster of differentiation 24 (CD24) is a human protein encoded by the CD24 gene which maps to chromosome 6q21. It is a small highly-glycosylated protein that is attached to the cell membrane via a glycosylphosphatidylinositol (GPI) anchor. Various studies have proven that CD24 is overexpressed in many human tumours, and its expression level has been found to be associated with a poor prognosis. Recently, CD24 has also been identified as a stem cell marker in several types of cancer. However little is known about CD24’s biological role in cancer or the mechanism through which it acts in cancer development. Thus, the main aim of this study is to investigate the potential functional role and signalling pathways of CD24 in various cancer models, such as colorectal cancer (CRC), pancreatic cancer, liver cancer, and lung cancer.